On the acceptability of the ambient tax mechanism: an experimental investigation - Kene Boun My; François Cochard; Anthony Ziegelmeyer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Our objective in this paper is to assess the acceptability of the ambient tax. Concretely, we ask subjects to choose between (A) an ambient tax and (B) an individual tax system. In case (A), they actually participate in a game in which their payo depends on all participants' decisions and on natural variability as would be the case in the real world if an ambient tax was implemented. In case (B) they simply earn a sure payo ; which is supposed to re ect their maximal pro t under the individual tax system. We take the percentage of agents preferring the ambient tax to a given sure payo level as an indicator of the acceptability of the ambient tax given this sure payo level. Our experimental results mitigate the common belief that am- bient taxes are totally unacceptable. If the sure alternative to the ambient tax policy is very costly for the polluters, for example because it involves high inspection costs, polluters might eventually prefer being liable to an ambient tax.
Keywords: C92; H3; Q5; 330; Nonpoint Source Pollution; Group Decision Making; Experiments; Acceptability of scal instruments; Umweltabgabe; Ökosteuer; Steuersystem; Gruppenentscheidung; Spieltheorie; Test